Association of Helicobacter pylori infection with gastroesophageal reflux disease. Issue 2 (February 2019) - Jie, Wu; Qinghong, Xu; Zhitao, Chen
Objective: Many studies have shown that Helicobacter pylori ( Hp ) is negatively correlated with gastroesophageal reflux disease (GERD). Moreover, some studies deny that eradication of Hp increases the incidence of GERD. Therefore, we investigated the association of Hp infection with GERD. Methods: In this retrospective analysis, patients with peptic ulcers were used as a blank control group. We used logistic regression to analyze the relationship between Hp infection and GERD. We analyzed 953 patients with peptic ulcers, 180 patients with both peptic ulcers and GERD, and 298 patients with GERD. Results: Among the patients with GERD, 75.6% (136/180) and 36.2% (108/298) of those with and without peptic ulcers, respectively, had Hp infection, and the difference was statistically significant. Among patients with peptic ulcers, 75.6% (136/180) and 67.4% (642/953) of those with and without GERD, respectively, had Hp infection. The incidence of GERD in patients with Hp- positive and -negative peptic ulcers was 17.5% (136/778) and 12.4% (44/355), respectively. These differences were also statistically significant. Conclusion: In the analysis of patients with GERD, the prevalence of Hp infection was higher among patients with than without peptic ulcers.